Telomere length in alcohol dependence: A role for impulsive choice and childhood maltreatment. (September 2017) - Kang, Jee In; Hwang, Syung Shick; Choi, Jong Rak; Lee, Seung-Tae; Kim, Jieun; Hwang, In Sik; Kim, Hae Won; Kim, Chan-Hyung; Kim, Se Joo
Highlights: This study examined leukocyte telomere length (LTL) in men with alcohol dependence. We investigated LTL in relation to delayed discounting and childhood maltreatment. An interaction effect of delay discounting and childhood maltreatment on LTL existed. Impulsive choice in alcoholics with high childhood trauma is related to short LTL. Abstract: Telomere shortening, a marker of cellular aging, has been considered to be linked with psychosocial stress as well as with chronic alcohol consumption, possibly mediated by oxidative stress and inflammatory response. Recent findings suggested that early life adversity on telomere dynamics may be related to impulsive choice. To further our understanding of the association of impulsive choice and childhood trauma on telomere length, we examined whether delayed discounting and childhood trauma or their interaction is related to leukocyte telomere length, while controlling for multiple potential confounding variables, in patients with alcohol dependence who are considered to have higher impulsive choice and shorter telomere length. We recruited 253 male patients with chronic alcohol dependence. All participants performed the delay discounting task, and the area under curve was used as a measure of delay discounting. Steeper delay discounting represents more impulsive choices. The modified Parent-Child Conflict Tactics Scale was used to measure childhood maltreatment. In addition, confounding factors, including socio-demographic characteristics, the Alcohol Use Disorders Identification Test, the Buss-Perry Aggression Questionnaire, the Resilience Quotient, the Beck Depression Inventory, and the Beck Anxiety Inventory, were also assessed. Hierarchical regression analyses showed a significant main effect of delay discounting (β = 0.161, t = 2.640, p = 0.009), and an interaction effect between delay discounting and childhood maltreatment on leukocyte telomere length (β = 0.173, t = 2.138, p = 0.034). In subsequent analyses stratified by childhood maltreatment, patients with alcohol dependence and high childhood trauma showed a significant relationship between delay discounting and leukocyte telomere length (β = 0.279, t = 3.183, p = 0.002), while those with low trauma showed no association between them. Our findings suggest that higher impulsive choice is associated with shorter telomere length, and childhood trauma may exert a moderating effect in the relationship between impulsive choice and telomere length.